Metabolomic Pathways Predicting Labor Dystocia by Maternal Body Mass Index - Carlson, Nicole S.; Frediani, Jennifer K.; Corwin, Elizabeth J.; Dunlop, Anne; Jones, Dean (American Journal of Perinatology Reports, 2020)
Objectives The purpose of this study was to evaluate the metabolic pathways activated in the serum of African-American women during late pregnancy that predicted term labor dystocia.Study Design Matched case–control study (n = 97; 48 cases of term labor dystocia and 49 normal labor progression controls) with selection based on body mass index (BMI) at hospital admission and maternal age. Late pregnancy serum samples were analyzed using ultra-high-resolution metabolomics. Differentially expressed metabolic features and pathways between cases experiencing term labor dystocia and normal labor controls were evaluated in the total sample, among women who were obese at the time of labor (BMI ≥ 30 kg/m2), and among women who were not obese.Results Labor dystocia was predicted by different metabolic pathways in late pregnancy serum among obese (androgen/estrogen biosynthesis) versus nonobese African-American women (fatty acid activation, steroid hormone biosynthesis, bile acid biosynthesis, glycosphingolipid metabolism). After adjusting for maternal BMI and age in the total sample, labor dystocia was predicted by tryptophan metabolic pathways in addition to C21 steroid hormone, glycosphingolipid, and androgen/estrogen metabolism.Conclusion Metabolic pathways consistent with lipotoxicity, steroid hormone production, and tryptophan metabolism in late pregnancy serum were significantly associated with term labor dystocia in African-American women.
Keywords: labor dystocia; obesity; mechanisms; metabolomics; parturition